Assessment of the level of vocational skills of young adults with intellectual disabilities : basis for instructional enhancement - Del Moro, Madonna A. (Manila : National University, 2010)
The study focused on the level of vocational skills of the YAID who are enrolled in SPED Center, Batino Elementary School for the school year 2009-2010. The vocational skills of these YAID that had been assessed includes; beadworks, paper folding, sewing, preparing simple and easy foods and cooking.
Title Page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of Contents -- List of Tables -- List of Figures -- Chapter 1: The Problem and its Setting -- Chapter 2: Review of Related Literature and Studies -- Chapter 3. Research Methodology -- Chapter 4. Presentation, Analysis and Interpretation -- Chapter 5. Summary, Conclusions and Recommendations -- Bibliography -- Appendices -- Curriculum Vitae .
Research Method: Descriptive Design.
Includes bibliographical references.